Motivation and depression rates in wheelchair basketball athletes (Research, Society and Development, 2020)
Objective: To evaluate the motivation for the practice of sports and levels of depression of athletes who are part of a wheelchair basketball team in a city in the interior of the state of Paraná. Methodology: For the evaluation of motivation, the Inventory of Motivation for Regular Physical Activity - IMPRAF 54 was used and for the depression indices, the Beck Depression scale was used. Eleven individuals were evaluated, wheelchair basketball athletes with different types of physical disabilities and experience in the sport. Results: As a result, it is observed that the motivation indices are related on a larger scale only in the aspects of health, pleasure and to minimize stress, the depression indices among athletes are low, a factor that is not determinant for a concern generalized about the wheelchair basketball team. Finals Considerations: The most relevant motivation index for athletes is the health aspect, while the least motivational within these aspects is that of competition. Depression rates show that a low level of depression occurs among athletes.